ABL Kinase Domain Mutations in Patients with Chronic Myeloid Leukemia in Jordan - Awidi, Abdalla (Mary Ann Liebert, Inc., 2012)
Mutations of the BCR-ABL tyrosine kinase domain constitute a major cause of resistance to tyrosine kinase inhibitors in patients with chronic myelogenous leukemia (CML). In this study, we analyzed peripheral blood samples from 185 Jordanian CML patients for ABL mutations, who were on imatinib for a minimum of 6 months regardless of their disease status and over a period of 5 years. Mutations were detected by nested RT–polymerase chain reaction, followed by direct sequencing of the ABL kinase domain. Twelve different point mutations were detected 25 times in 21 patients. The resultant mutations were as follows: four patients have T315I, three of each of the following: L248V, F317L, and G250E, two of each of the following: H396R, M244V, and T277A, and one of each of the following: F311I, M318T, Q252H, F359A, F359I, and Y326H. After patient follow-up, the mutation had disappeared in 12 patients; 3 patients died; 3 patients were not retested; and 3 patients had persistent mutation. The finding of our study is in line with what has been described in the literature. Detecting ABL mutations in chronic phase may lead to positive outcome by modifying treatment.